Malaysian public perception on passenger standing cabin for commercial transport aircraft in domestic flights - Dasuki, Norhafizah; Romli, Fairuz Izzudin (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
With the increase in market competition among the airlines today, many of them are looking for new alternative ways to reduce the cost for their flight operations in order to offer more affordable flight services. One of the proposals that have been put forward is passenger standing cabin concept, which is expected to increase cabin capacity and reduce flight cost per passenger per flight. The perception and also reception of the Malaysian public regarding the potential implementation of this new standing cabin concept by the domestic airlines are explored through conducted public survey. The survey has been carried out at two key domestic hub airports for local low-cost airlines in Malaysia: Sultan Abdul Aziz Shah Airport and Kuala Lumpur International Airport 2. From the collected data, the Malaysian public responses are taken as encouraging and this finding highlights the existence of market demands for this standing cabin concept. The support for this new cabin idea appears to be dependent on the social demographic background of the public, with age, gender and income level are among some of the main indicators. Several factors that could improve the market acceptance of this new cabin concept are also established from the survey data such as ticket price, comfort and safety aspects.